You never know, half the work may have been done already. Will the Utrecht Documentation system become a national knowledge institute? (Bulletin KNOB, 2003)
Half the time available for a research is often spent on trying to figure out what later on appears to have been known for a long time. The Utrecht Documentation System (UDS) was set up as a very special extra access to the information that is scattered in many places. Although the set-up is intended for the entire Netherlands, the system contains a lot of information on the city of Utrecht in particular.An example. At the end of the 19th century Lange Viestraat in Utrecht was widened on the north side and in the thirties of the 20th century on the south side; this causes problems during historical research. According to the recent catalogue of the Centraal Museum the stone tablet ‘In den royen os, 1639’ comes from Lange Viestraat 4. Building-historical research in this building will not provide the context. The tablet comes from a building that was demolished in 1906, situated 25 metres east of no. 4, exactly in the place of the present road surface. Sorting out all the addresses on both sides of the street, before and after the demolition, took half a year. But all the old construction drawings are in the right place now and it was worth the trouble.For over 20 years the motivation of the group of volunteers working at the UDS has been to promote respectful dealing with the cultural heritage, based on an understanding of the history of the built environment. The documentation system is a means thereto. Initially, it was organised as a paper encyclopaedia for Utrecht. The series of folders now takes up 20 metres' space and is situated in Utrecht. As in the meantime important information is available for the entire Netherlands, a start has now been made on the internet via the website www.documentie.org.The purpose of the site is to provide or show the way to answers, in words and pictures, to questions related to the conservation of monuments in the widest sense of the word. Both laymen and experts belong to the target group. It concerns the whole range, from arousing interest to promoting scientific research.The site offers reading lists, often also texts and illustrations. Even those who cannot quite figure out what exactly they want to ask, will be assisted as much as possible, e.g. by plans you can click and the catchword 'zoekplaat' (picture puzzle). A lot of attention is devoted to links to other sites, from which the information searched for can be shown directly.Thus the way is shown to information of both co-ordinating organisations and local initiatives. The ideal is not one central site for culture, but a network of private and public initiatives freely communicating with each other.